The Study of Mutelu Tourism to Respond to the Chinese Market in Chiang Mai Province - Jinasot , Nattanicha; Numtong, Kanokporn (Journal of Ecohumanism, 2024)
This article aims to study the state of mutelu tourism in response to the Chinese market in Chiang Mai Province through a combination of both qualitative and quantitative methods. The population comprised 145 Chinese tourists visiting Mutelu tourist attractions in the Chiang Mai Province. The data were collected through a questionnaire and an interview with a purposive sample group of tenexperts in amulet marketing in Chiang Mai. It was found that the majority of tourists were female aged 25−35, holding a bachelor's degree, reflecting differences in values, attitudes, and ideas across age groups. Of the Chinese tourists, 97.24% visited the Mutelu tourist attractions. The most popular Mutelu spots in Chiang Mai were: 1) Wat Phra That Doi Suthep, 2) Wat Phra Singh, (3) W at Doi Kham, among others. The purpose of their visits was predominantly to pay respect and acquire amulets for financial prosperity and fortune, accounting for 59.31% of the total . The popularity of these destinations among Chinese tourists can be attributed to the following factors: (1) serving both sightseeing and Mutelu purposes, (2) having good service, (3) having testimonials by famous figures that had sparked interests, (4) being Chiang Mai's landmarks with interesting histories and easily accessible locations, and (5) being established as a result of reverence for renowned respectable monks. Other factors affecting tourists' decisions were: (1) seeking a spiritual anchor to enhance mental well-being, (2) similarities between Chinese and Thai beliefs, and (3) following recommendations by celebrities and well-known figures.